Law and Socio-Environmental Responsibility - Foy Valencia, Pierre (2010)
The author focuses on social responsibility from the legal angle given that imputations can be given for the breach of obligations. In this way, the article begins by showing the background of the SR in which he underwent a paradigm shift from the altruistic or philanthropic concept to the socio-environmental concept. The aforementioned change shows that the RS does not only correspond to the interests of the company-shareholders-but also involves all the members of the company- stakeholders. Second, the author explores the different definitions of the concept of social responsibility, including the approaches of the Green Paper, the Red Forum and other contributions of the international community. Now it is important to highlight the interrelation between socio-environmental responsibility and Law. As a result, national legislation and case law are mentioned as they contribute to an adequate constitutional framework. Based on this, the author emphasizes that the stability of the company is generated not only from the State but also from the participation of the same companies that should be the protagonists. Added to this, is the infra-constitutional regulation in which the General Environmental Act stands out. Finally, the author comments on three mechanisms to motivate the business sector: standards with technology performance standards, economic self-regulation, economic instruments in government intervention. In conclusion, the author proposes that both legal norms and voluntary standards have a legal approach that contributes to the application of standards.